Vasomotor responses are similar between outbred UM-HET3 and inbred C57BL/6J male and female mouse mesenteric resistance arteries - Looft-Wilson, Robin C.; Naraynan, Surya; Salmon, Kathleen; Wunibald, Ethan; Simmons, Brian; Haitz, Connor; Shah, Vishakha; Xu, Margaret (Frontiers in Physiology, 2025)
ObjectiveGenetically diverse UM-HET3 (HET3) mice have emerged as a more robust model of human large artery dysfunction than the commonly used inbred C57BL/6J (C57) mice. However, HET3 resistance artery function has not been examined. The purpose of this study was to examine HET3 versus C57 mesenteric resistance artery agonist-induced vasomotor responses to phenylephrine (PE) and acetylcholine (ACh), PE-induced myoendothelial feedback (endothelium-dependent feedback dilation to PE-induced vasoconstriction) and its underlying mechanisms, and eNOS (an enzyme involved in endothelium-dependent dilation) expression.HypothesisVasomotor responses, mechanisms, and eNOS protein expression would be similar between HET3 and C57 mesenteric resistance arteries of both sexes.MethodsFirst- and second-order mesenteric arteries from male and female (8–18 weeks old) HET3 and C57 mice were isolated and cannulated for pressure myography. The luminal diameter was measured (in a group-blinded manner) during cumulative addition of PE [10−9–10−5 M] and then ACh [10−10–10−4 M]. In separate arteries, myoendothelial feedback was measured by diameter responses (constriction followed by endothelium-dependent feedback dilation) to 10−5 M PE over 20 min, ± nitric oxide synthase (NOS) inhibition (10−5 M L-NAME) and ± hyperpolarization inhibition with 35 mM KCl to assess myoendothelial feedback mechanisms. eNOS protein expression was measured by Western blot.ResultsArteries from all groups were similar in size (group mean range: 213–218 µm) and exhibited negligible basal tone (group mean range: 1%–4% constriction). PE-induced peak vasoconstriction (range: 71.0%–73.8% constriction; n = 11–12) and EC-50’s (range: 1.03–1.54 µM) were similar between groups. ACh-induced peak vasodilation (range: 63.1%–73.4% dilation) was also similar between groups. However, ACh EC-50 was significantly (p < 0.05; ANOVA, Bonferroni) lower in HET3 female (0.047 ± 0.021 µM) than in C57 female arteries (4.22 ± 1.97 µM) (p < 0.05). Myoendothelial feedback responses were similar between groups (group mean range: 23.3%–34.0% dilation) at 10 min, but responses were significantly (p < 0.01) greater in HET3 males (56.5% ± 4.9%) than in C57 male arteries (38.8% ± 2.2%) at 20 min (n = 12–15), and they were predominantly dependent on hyperpolarization mechanisms. eNOS/GAPDH and eNOS/total protein expression were similar between the groups.SignificanceIn this study, HET3 mesenteric resistance arteries were found to exhibit vasomotor responses similar to those of C57 arteries, with some indications of greater endothelium-dependent vasodilation in HET3, making it a viable mouse model for vascular studies.